A randomized phase I trial evaluating the effects of inhaled 50–50% N2O–O2 on remifentanil‐induced hyperalgesia and allodynia in human volunteers. (31st March 2016) - Wehrfritz, A.; Schaefer, S.; Troester, A.; Noel, N.; Bessiere, B.; Apiou‐Sbirlea, G.; Simonnet, G.; Schuettler, J.; Richebé, P.
Abstract: Background: Opioids are known to relieve pain, and also aggravate pre‐existing hyperalgesia. In animal studies, the N‐ methyl‐d ‐aspartate‐receptor antagonist nitrous oxide (N2 O) was able to prevent hyperalgesia. The present study evaluated the effect of N2 O on hyperalgesia after remifentanil infusion in healthy volunteers. Methods: Twenty‐one healthy volunteers were enrolled in this placebo‐controlled cross‐over study. Transcutaneous electrical stimulation at high current densities induced spontaneous acute pain and stable areas of hyperalgesia. Each volunteer underwent the following four sessions: (1) 50–50% N2 –O2 and i.v. saline; (2) 50–50% N2 –O2 and i.v. remifentanil 0.1 μg/kg/min; (3) 50–50% N2 O–O2 and i.v. saline; (4) 50–50% N2 O–O2 and i.v. remifentanil 0.1 μg/kg/min. Inhaled gas mixtures lasted for 60 min, i.v. drug administration for 30 min. Visual analogue scale pain intensity, areas of pinprick hyperalgesia and touch‐evoked allodynia were assessed repeatedly for 160 min. Results: Data of 19 volunteers were analysed. There were significant time and treatment effects regarding areas of hyperalgesia and allodynia ( p < 0.02). The area of hyperalgesia was significantly reduced in the N2 O + remifentanil session compared to the remifentanil session (35.88 ± 22.37 vs. 43.55 ± 18.48 cm 2, p = 0.004). The area of allodynia was significantly reduced in the N2 O + remifentanil session compared to the remifentanil session (29.95 ± 16.15 vs. 34.80 ± 15.35 cm 2, p = 0.008). The pain intensity was significantly reduced in the N2 O + remifentanil session compared to the remifentanil session (37.96 ± 12.78 vs. 42.15 ± 13.34 mm, p < 0.0001). Conclusions: Nitrous oxide significantly reduced hyperalgesia, allodynia and pain intensity aggravated after remifentanil administration in a human volunteer model. What does this study add?: This study brings the evidence that N2 O reduces the remifentanil aggravated secondary hyperalgesia in human volunteers exposed to a well‐known model of electrical pain. N2 O was able to oppose the hyperalgesia, the allodynia and the pain intensity consecutive to remifentanil use in this specific pain model.